Improving stego key using extended-1 and extended-2 techniques of feature coding method in text steganography - Utama, Sunariya (2024)
This study focuses on implementing steganography in the text domain called text steganography. Many previous researchers utilize a method in text steganography called the feature coding method to conceal the hidden message based on the uniqueness of the letter in the text. It highlights some feature coding methods that are applied alphabet A-Z letters. However, the existences of technique in feature coding method are easily to recognize due the obvious group of letter pattern text in chosen hidden message. Therefore, the objective is to propose the feature coding of text steganography using binary bit representation. It chose specific group letter for the stego key that begins with identifying the scheme of this technique. Subsequently, this study develops an extension technique that adapts the existing techniques of feature coding method. The proposed extended technique consists of Extended-1 and Extended-2 techniques of feature coding method. It compares the existing and extended techniques feature coding that is evaluated using some parameters to assess performance of technique. The experimental results show that the Extended-1 technique has the highest capacity ratio performance, with 100% recall rate, 46.15% F-measure rate, and 30% precision and accuracy rates. Meanwhile, the Extended-2 technique exhibits the highest robustness and security performance, achieving 100% performance for precision, recall, accuracy, and F-measure rates. The output of this study generates the extended technique in feature coding that is expected to contribute to the improvement of text steganography. For future work, the technique's utilization of feature coding method in artificial intelligence tools to enhance information security and also as a current trend in the IT field.